Technical Efficiency Analysis of Millet Production in the Sahel Region of Burkina Faso - SEOGO, Windinkonté; SAWADOGO, W. Jean-Pierre (Journal of Social and Development Sciences, 2020)
Millet is the basic cereal crop which contributes to rural households’ food security in the Sahel region of Burkina Faso. This study assesses the technical efficiency and its determinants of millet farmers in this region. A stochastic frontier approach is followed to analyze data collected on 106 households randomly selected in 2017. The mean technical efficiency is estimated at 71.23% implying that millet production may be increased by 28.77% with the same resources used by farmers. The results show that formal education, off farm income, breeding, and access to credit are the main factors affecting the production efficiency. The study recommends decisions makers to take appropriate measures regarding these factors, to enhance millet productivity in the Sahel region.